An Interactive Model of Communication between Abiotic Nanodevices and Microorganisms. Issue 42 (19th September 2019) - de Luis, Beatriz; Llopis‐Lorente, Antoni; Rincón, Paola; Gadea, José; Sancenón, Félix; Aznar, Elena; Villalonga, Reynaldo; Murguía, José Ramón; Martínez‐Máñez, Ramón
Abstract: The construction of communication models at the micro‐/nanoscale involving abiotic nanodevices and living organisms has the potential to open a wide range of applications in biomedical and communication technologies. However, this area remains almost unexplored. Herein, we report, as a proof of concept, a stimuli‐responsive interactive paradigm of communication between yeasts (as a model microorganism) and enzyme‐controlled Janus Au–mesoporous silica nanoparticles. In the presence of the stimulus, the information flows from the microorganism to the nanodevice, and then returns from the nanodevice to the microorganism as a feedback. Abstract : If yeasts could talk : An interactive paradigm of communication between yeasts and enzyme‐controlled Janus Au–mesoporous silica nanoparticles is reported. The fluorescent signal from the microorganism (corresponding to the production of green fluorescent protein) is governed by the biunivocal communication with the nanodevice through enzymatic reactions and the exchange of chemical messengers.